Immediate Enhancement of Nerve Function Using a Novel Axonal Fusion Device After Neurotmesis. Issue 6 (December 2017) - Riley, David Colton; Boyer, Richard B.; Deister, Curt A.; Pollins, Alonda C.; Cardwell, Nancy L.; Kelm, Nathaniel D.; Does, Mark D.; Dortch, Richard D.; Bamba, Ravinder; Shack, Robert Bruce; Thayer, Wesley P.
Abstract : Background: The management of peripheral nerve injuries remains a large challenge for plastic surgeons. With the inability to fuse axonal endings, results after microsurgical nerve repair have been inconsistent. Our current nerve repair strategies rely upon the slow and lengthy process of axonal regeneration ( 1 mm/d). Polyethylene glycol (PEG) has been investigated as a potential axonal fusion agent; however, the percentage of axonal fusion has been inconsistent. The purpose of this study was to identify a PEG delivery device to standardize outcomes after attempted axonal fusion with PEG. Materials and Methods: We used a rat sciatic nerve injury model in which we completely transected and repaired the left sciatic nerve to evaluate the efficacy of PEG fusion over a span of 12 weeks. In addition, we evaluated the effectiveness of a delivery device's ability to optimize results after PEG fusion. Results: We found that PEG rapidly (within minutes) restores axonal continuity as assessed by electrophysiology, fluorescent retrograde tracer, and diffusion tensor imaging. Immunohistochemical analysis shows that motor axon counts are significantly increased at 1 week, 4 weeks, and 12 weeks postoperatively in PEG-treated animals. Furthermore, PEG restored behavioral functions up to 50% compared with animals that received the criterion standard epineurial repair (control animals). Conclusions: The ability of PEG to rapidly restore nerve function after neurotmesis could have vast implications on the clinical management of traumatic injuries to peripheral nerves.